2020
DOI: 10.1038/s41467-020-17197-2
|View full text |Cite
|
Sign up to set email alerts
|

Suprachiasmatic VIP neurons are required for normal circadian rhythmicity and comprised of molecularly distinct subpopulations

Abstract: The hypothalamic suprachiasmatic (SCN) clock contains several neurochemically defined cell groups that contribute to the genesis of circadian rhythms. Using cell-specific and genetically targeted approaches we have confirmed an indispensable role for vasoactive intestinal polypeptide-expressing SCN (SCN VIP) neurons, including their molecular clock, in generating the mammalian locomotor activity (LMA) circadian rhythm. Optogenetic-assisted circuit mapping revealed functional, di-synaptic connectivity between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 100 publications
(116 reference statements)
4
106
0
Order By: Relevance
“…SCN VIP neurons represent integration points for both photic and non-photic sensory inputs (Acosta-Galvan et al, 2011). The activation of SCN VIP neurons by bilateral injections of Cre-dependent hM3Dq into the SCN of heterozygous VIP-Cre mice at ZT4 and ZT13 does not change locomotor or sleep-wake cycle phenotypes (Todd et al, 2020). Hence, we asked whether selective inhibition of SCN VIP neurons may be able to simulate the effect of ZT0-4 TRF entrainment (i.e., delay the offset of activity).…”
Section: Resultsmentioning
confidence: 99%
“…SCN VIP neurons represent integration points for both photic and non-photic sensory inputs (Acosta-Galvan et al, 2011). The activation of SCN VIP neurons by bilateral injections of Cre-dependent hM3Dq into the SCN of heterozygous VIP-Cre mice at ZT4 and ZT13 does not change locomotor or sleep-wake cycle phenotypes (Todd et al, 2020). Hence, we asked whether selective inhibition of SCN VIP neurons may be able to simulate the effect of ZT0-4 TRF entrainment (i.e., delay the offset of activity).…”
Section: Resultsmentioning
confidence: 99%
“…The SCN is a pair of nuclei located in the anterior hypothalamus, situated directly dorsal to the optic chiasm and lateral to the third ventricle. It is comprised of approximately 20,000 heterogenous neurons that secrete dozens of neuropeptides, neurotransmitters, and cytokines, many of which can be at least partially co-expressed by certain populations of SCN neurons ( Figure 2 ; Abrahamson and Moore, 2001 ; Cheng et al, 2002 ; Antle and Silver, 2005 ; Todd et al, 2020 ; Wen et al, 2020 ). The SCN is classically divided into two subregions, a light-responsive ventrolateral “core” and a rhythmic dorsomedial “shell,” based on the neurochemical nature of cells in each area and its physiological function ( Aton et al, 2005 ).…”
Section: Scn Structure and Connectivitymentioning
confidence: 99%
“…GRP can also act as a secondary synchronizing neuropeptide when VIP-VPAC2 signaling is defective, since addition of GRP to Vpac2 –/– SCN explants can transiently restore network synchrony ( Brown et al, 2005 ; Maywood et al, 2011 ). Recent single cell RNAseq studies have found that GRP-expressing neurons are a subpopulation of VIP neurons: approximately one-quarter of VIP + cells in the SCN co-express GRP ( Todd et al, 2020 ; Wen et al, 2020 ).…”
Section: Intra-scn Communication and Signalingmentioning
confidence: 99%
“…These VIP core neurons then appear to entrain the rhythmicity of AVP shell neurons and other SCN neuronal cell types in order to establish SCN-level synchrony (Aton et al, 2005;Maywood et al, 2006). The subpopulation of SCN neurons expressing NMS have also been implicated as playing a crucial role in circadian pacemaking (Lee et al, 2015), however, more recent work suggests that the critical neurons in this role belong to a molecularly distinct subpopulation that expresses both NMS and VIP together (Todd et al, 2020). Interestingly, Todd et al (2020) found that SCN VIP neurons that also contain NMS are enriched with the transcript Per2 associated with a core clock gene, whereas the non-NMS subpopulation of SCN VIP neurons that also contain GRP did not have such transcripts.…”
Section: The Extended Mammalian Circadian Timing Systemmentioning
confidence: 99%
“…The subpopulation of SCN neurons expressing NMS have also been implicated as playing a crucial role in circadian pacemaking (Lee et al, 2015), however, more recent work suggests that the critical neurons in this role belong to a molecularly distinct subpopulation that expresses both NMS and VIP together (Todd et al, 2020). Interestingly, Todd et al (2020) found that SCN VIP neurons that also contain NMS are enriched with the transcript Per2 associated with a core clock gene, whereas the non-NMS subpopulation of SCN VIP neurons that also contain GRP did not have such transcripts. Altogether, this suggests that SCN VIP neurons are composed of both pacemaker and non-pacemaker subpopulations, which is supported by previous work demonstrating that SCN VIP neurons can be divided into two groups based on the lightinducibility of clock genes, innervation of retinal afferents, day-night variability of VIP mRNA, and coexpression of GRP (Kawamoto et al, 2003).…”
Section: The Extended Mammalian Circadian Timing Systemmentioning
confidence: 99%